Human sacrifice and value. (August 2019) - Løvschal, Mette; Gullbekk, Svein Harald; Johansen, Mette-Louise; O'Neill, Sean; Walsh, Matthew; Willerslev, Rane
Abstract: Abstract : Human sacrifice is a well-attested and much mythologised phenomenon of human society, but what constitutes human sacrifice? Why is socially sanctioned violence considered sacrifice? And why are human lives sacrificed? New research uses archaeological case studies from Scandinavia to understand performative violence.